Representasi Budaya Bali Pada Kemasan Kopi EL’S COFFE - Swatriani, Rinkapati; Arimbawa, I Made Gede (Visualita Jurnal Online Desain Komunikasi Visual, 2024)
To mention of coffee in Indonesia can be enjoyed by Indonesian coffee lovers, it is necessary to provide packaging that has a concept of applying Indonesian culture that can represent the identity of the coffee producing region. One of the coffee products that applies cultural representation in packaging is El's Coffee. The two focuses of this research are the cultural representation displayed in the packaging as the identity of the El's Coffee Kintamani series coffee products and the structure and materials of the packaging. The results of the analysis can be concluded that the visual elements contained in El's Coffee packaging can represent elements of Balinese culture that are commonly found and familiar to the wider community. The easiest thing to recognize is the temple building in the middle of the package. Apart from that, the visual of a dancer also strengthens this representation. The attributes used by dancers are characteristics of Balinese dancers. The packaging structure is designed to make it easier for consumers to carry and open the packaging. With sizes adapted to the anatomy of an adult human hand. The materials used differ between tertiary, secondary and primary packaging because they are adjusted to the needs for packaging the product.